Productivity improvement of tower crane in tall buildings - Manrique, A. (2020)
The tower crane is an electromechanical equipment that is used for the vertical transport of materials in a construction project and together with the two riggers form the work team to carry out this task. One of the main problems in the construction of multifamily buildings corresponds to the use of the tower crane because vertical transport causes non-contributory times, which is, dead times and waits above expectations. This research analyzes the current vertical transport process and proposes its optimization through some management tools with the aim of improving the productivity of the use of the tower crane by reducing non-contributory times. To this end, the productivity of the work team is recorded in several projects with similar characteristics, then the main problems are selected to analyze them and finally the process is optimized. The results determined that non-contributory times can be reduced by 10% if there is an orderly and continuous process.